2016
DOI: 10.3389/fmicb.2016.01895
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Methanogenic and Methanotrophic Communities to Elevated Atmospheric CO2 and Temperature in a Paddy Field

Abstract: Although climate change is predicted to affect methane (CH4) emissions in paddy soil, the dynamics of methanogens and methanotrophs in paddy fields under climate change have not yet been fully investigated. To address this issue, a multifactor climate change experiment was conducted in a Chinese paddy field using the following experimental treatments: (1) enrichment of atmospheric CO2 concentrations (500 ppm, CE), (2) canopy air warming (2°C above the ambient, WA), (3) combined CO2 enrichment and warming (CW),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Higher Ts generally had a negative effect on NME (Fig 5c & d). Higher soil temperatures increase the oxidation potential of methanotrophs (Liu et al, 2016;King and Adamsen, 1992), so this result was expected for the drier portions of the basin and upland tundra. However, this wasn't expected for the sedge areas because most studies find NME in sedges is positively correlated to Ts (Olefeldt et al, 2013).…”
Section: Nme Response To Environmental Factors and Vegetation Typementioning
confidence: 88%
“…Higher Ts generally had a negative effect on NME (Fig 5c & d). Higher soil temperatures increase the oxidation potential of methanotrophs (Liu et al, 2016;King and Adamsen, 1992), so this result was expected for the drier portions of the basin and upland tundra. However, this wasn't expected for the sedge areas because most studies find NME in sedges is positively correlated to Ts (Olefeldt et al, 2013).…”
Section: Nme Response To Environmental Factors and Vegetation Typementioning
confidence: 88%
“…The depth of the sediment layers shape the structure of the methanogenic communities and also determine the pathway of CH 4 production. The CH 4 produced from the freshwater lakes are the result of the microbial methanogenesis occurring there .…”
Section: Methanogenesis In Freshwater Lacustrine Ecosystemsmentioning
confidence: 99%
“…Therefore, soil organic C quantity and quality changes due to elevated CO 2 could affect the fungal diversity indices. Our previous studies also reported that elevated CO 2 increased the SOC and microbial biomass C by stimulating the primary biomass production of rice and increasing the abundance of microorganisms (Liu et al 2014;Liu et al 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Compared with the ambient conditions, elevated CO 2 and warming resulted in higher levels of organic C, root exudates, and microbial abundance and diversity. This results in more complex niches for microbial communities (Bhattacharyya et al 2013, Liu et al 2016Wang et al 2017), which may enhance the interactions among microbial communities in the crop root zone. Recently, a long-term warming experiment showed that warming enhanced the complexity and stability of the microbial network, which could be tightly related to ecosystem function processes (Yuan et al 2021).…”
Section: Discussionmentioning
confidence: 99%